HISTORY OF “CORPORATE SOCIAL RESPONSIBILITY” CONCEPT - FARCANE, Nicoleta; BUREANA, Eusebiu (Annales Universitatis Apulensis Series Oeconomica, 2015)
With long-lasting debates, corporate social responsibility concept was from the beginning a high-interest subject to all of the stakeholders of the companies: shareholders, public opinion, employees and governments. Based on studies which demonstrates the socially responsible companies have major financial and image-related benefits, we started researching the roots of the concept “corporate social responsibility”. By using qualitative method, hermeneutic perspective, we chose the comprehensive approach of CSR developed by Goodpaster et al. (2005). We analyzed four sides out of five of the concept (economics contributions of companies to society, contextual changing of companies’ development and existence environment, Conceptual evolution and dimentions of CSR, perspective of theories in close connection with CSR) and we proposed a definition of what we belive is CSR. Analyzing the pros and cons of accepting the CSR model as stated nowadays, we concluded as follows: Without neglecting the implicit social responsibility of companies towards others (like human beings) – by means of taxes and social charges imposed by law, and without fully accepting the extreme opinion that presents corporations as entities that indirectly hold all the communities’ political, social and economic power, companies should strictly follow their economic goal, which implicitly fulfils all the additional requirements imposed to companies by some stakeholders.